Who's Buying Groceries. (Who's buying series., 2015)
The twelfth edition of Who's Buying Groceries is based on unpublished data collected by the Bureau of Labor Statistics' 2013 Consumer Expenditure Survey--you can't get these data online. It examines how much Americans spend on food at grocery and convenience stores by the demographics that count: age, income, high-income households, household type, race and Hispanic origin, region of residence, and education. To round out the spending picture, it also presents who-are-the-best-customers analyses of the data, showing the demographics of the best and biggest customers at a glance. The 80-plus items examined in this report range from bacon to coffee, cereal and the supermarket deli.